Correlation Analysis Of HIV Stadium With Opportunistic Infection In Pregnant Women At Ibnu Sina General Hospital Gresik - Elisanti, Alinea Dwi; Ardianto, Efri Tri (Journal of Global Research in Public Health, 2020)
HIV-AIDS is an infectious disease caused by infection with the Human Immunodeficiency Virus. HIV can be transmitted through sex, blood transfusions, sharing needles and mother-to-child transmission (perinatal). Heterosexual risk factors were the highest, namely 82.8%, followed by homosexuals by 7.4% and perinatal by 4.0%. At Gresik Regency in 2016, was found that the number of HIV sufferers had increased by 29% from 2015. This study aimed to identify the relationship between HIV Stadium and Opportunistic Infection in Pregnant Women At Ibnu Sina General Hospital Gresik. This non-reactive research use analytic cross-sectional design. Sample was taken using total sampling technique. Secondary data were taken since 2013- March 2018 using data collection sheets and analysis using chi-Square test (alpha: 0.05). The results showed there were 29 pregnant women with HIV-AIDS, 96.6% of patients came from Gresik Regency, and 3.4% from outside, the most of age group were > 25-30 years (34.5%), 96.6% of respondents had married, education was mostly high school (58.6%), most respondents (75.9%) had no opportunistic infections, HIV stadium at level asimtomatik reached 51.7% and simtomatik stadium level reach 48.3%. There was a correlation between the stadium of HIV and opportunistic infections with p-value 0.011. So that it needs optimal attention especially the provision of ART therapy and treatment of opportunistic infection in pregnant women